Investigation of Aloe Vera as active layer for development of organic based memory devices. (March 2015) - Lim, W. F.; Quah, H. J.; Sreenivasan, S.; Cheong, K. Y.
Abstract : This work had successfully employed commercially purchased Aloe Vera gel as the active layer on indium tin oxide (ITO) glass substrate. Different heating temperatures were studied on the Aloe Vera/ITO samples. Results showed the existence of OH and C–H groups in the samples using Fourier transform infrared spectroscopy. Typical thickness (246·8 nm) of Aloe Vera was determined using field emission scanning electron microscopy cross-sectional studies. Direct band gap ( E g ) energies (3·88–4·00 eV) were calculated using Tauc plot by extracting data from the UV-Vis absorption spectra while dielectric permittivity values were measured using impedance analyser. Current-gate voltage ( I–V ) characteristics and time dependence I–V characteristics of the Al/Aloe Vera/ITO device deduced that the device was showing a write-once-read-many (WORM) memory response and thus was potential to serve as the WORM memory device.